Prinsip Bagi Hasil Dalam Perbankan Syariah Menurut Hukum Islam - Mustafa, Mustafa (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
In Islamic bank operations, the main principle is to be free from usury (interest) and the application of profit sharing. The most fundamental principle in Islamic banks is free of the interest. Therefore, interest is a system that must be avoided by Islamic banks. For this reason, Islamic banks replace it with profit sharing. Islamic banking applies the business financing pattern with the principle of profit sharing, as one of the main points in Islamic banking activities will foster a sense of responsibility for each party, both banks and debtors, so that in carrying out its activities all parties will in principle pay attention to the principle of prudence and will minimize the risk of business failure. Then the Islamic bank has a profit sharing or risk of loss. The relationship between the depositor and the bank, as well as the relationship between the bank and the borrowing customer is the relationship of the work partner (partnership), therefore, the benefits obtained are shared together, according to the proportion of participation as partners. Vice versa, if there is a loss, it will be borne jointly among business partners in accordance with the proportions.